The Impact of repetition and recycling on grade 11 students' vocabulary retention at Long Hai-Phuoc Tinh High school - Phùng, Thị Lam (University of Languages and International Studies, 2017)
Chapter one reviews scholarly theoretical background to teaching and learning vocabulary in a second language. Chapter two deals with the methodology of this research in terms of the setting of the study, sampling participants, instruments and procedure of data collection. Chapter three devotes to the account of the study in terms of data analysis and findings interpreted from the results of the T-test and questionnaires.